Genetic characterisation of Measles virus variants identified during a large epidemic in Milan, Italy, March–December 2017. (2019) - Bianchi, S.; Frati, E.R.; Lai, A.; Colzani, D.; Ciceri, G.; Baggieri, M.; Lamberti, A.; Senatore, S.; Faccini, M.; Mazzilli, F.; Gramegna, M.; Zehender, G.; et al.
Abstract: In 2017, Italy experienced a large measles epidemic with 5408 cases and four deaths. As Subnational Reference Laboratory of the Measles and Rubella surveillance NETwork (MoRoNET), the EpiSoMI (Epidemiology and Molecular Surveillance of Infections) Laboratory (University of Milan) set up rapid and active surveillance for the complete characterisation of the Measles virus (Mv) responsible for the large measles outbreak in Milan and surrounding areas (Lombardy, Northern Italy). The aims of this study were to describe the genetic profile of circulating viruses and to track the pathway of measles transmission. Molecular analysis was performed by sequencing the highly variable 450 nucleotides region of the N gene (N-450) of Mv genome. Two-hundred and ninety-nine strains of Mv were analysed. The phylogenetic analysis showed five different variants, two not previously described in the studied area, belonging to D8 and B3 genotypes. Three events of continuous transmission of autochthonous variants (D8-Osaka, D8-London and B3-Milan variants) and two events of continuous transmission of imported variants (B3-Dublin and D8-Hulu Langat) tracked five different transmission pathways. These pathways outlined two epidemic peaks: the first in April and the second in July 2017. The correlation between Mv variant and the epidemiological data may enable us to identify the sources of virus importation and recognise long-lasting virus transmission pathways.